Exploring Ganweikang Tablet as a Candidate Drug for NAFLD Through Network Pharmacology Analysis and Experimental Validation - Ma, Chuanrui; Wang, Xinyu; Zhang, Jing; Zhao, Yun; Hua, Yunqing; Zhang, Chao; Zheng, Guobin; Yang, Guangyan; Guan, Jianli; Li, Huahuan; Li, Meng; Kang, Lin; et al. (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is defined as liver disease in which more than 5% of hepatocytes are steatotic with little or without alcohol consumption. NAFLD includes benign non-alcoholic fatty liver (NAFL) and non-alcoholic steatohepatitis (NASH). Importantly, NASH is an advanced progression of NAFL and is characterized by steatosis, hepatocyte ballooning, lobular inflammation, and fibrosis. However, to date, no drugs targeting specifically for NAFLD have been approved by the FDA. Therefore, a new drug or strategy for NAFLD treatment is necessary. However, the pathogenesis of NAFLD is complex and no single-target drugs have achieved the desired results. Noticeably, traditional Chinese medicine formulations is a complex system with multiple components, multiple targets, and synergistic effects between components. Ganweikang tablet is a compound formula based on traditional Chinese medicine theory and clinical experience. In this study, network pharmacology analysis indicates Ganweikang tablet as a candidate for NAFLD treatment. Furthermore, we evaluated the therapeutic effects of Ganweikang tablet on the NAFL and NASH and tried to clarify underlying molecular mechanisms in animal model and cell experiment. As expected, Ganweikang tablet was found to improve NAFL and NASH by modulating inflammation, apoptosis, and fatty acid oxidation through inhibiting NFB, caspase-8, and activating PPAR, which not only indicates that Ganweikang tablet as a drug candidate but also provides a theoretical basis of Ganweikang tablet for the treatment of NAFL and NASH.